Simulation and Test of Energy Consumption of High-Tc Superconducting Coils in Electromagnetic Levitation System - Jie Xu (IEEE, 2021)
In order to evaluate the energy consumption of the superconducting magnetic levitation system with real-time control, the methods of simulation and test were used to study the AC plus DC loss of the superconducting coil. The simulation established a 2D finite element model in COMSOL, which was based on the H equations method with simple form and fast calculation speed. The test was carried out on a new type of measurement system, which adopted the electrical method with high sensitivity, simple operation and easy implementation. The results of simulation and test showed that, under normal working conditions, the levitation current in the form of AC plus DC produced a relatively small energy loss below $1mW$ per meter. This conclusion is helpful for the promotion and application of superconducting magnetic levitation control system.